Effect of different annealing temperatures on microstructures and properties of Cu–Sn Alloy. (31st August 2018) - Fan, Wenxin; Hui, Jun; XinFeng, Zai; Gao, Weifeng; Xue, Chen
Abstract: Through an EBSD analysis on the change characteristics of the microstructure of a spinning formed thin-walled Cu–Sn alloy cylinder which is annealed at 300 °C–600 °C for 2 h, it indicates that the grain size increases with the rise of annealing temperature and the size falls back at 400 °C. At 300 °C, the microstructure is mainly composed of deformed grains. With the progress of recrystallization, the deformed grains disappear first, and the number of substructures gradually reduces but always exists. In terms of the grain boundary, the subgrain boundaries gradually disappear and the Σ9 grain boundary at the secondary peak gradually transforms into the Σ3 grain boundary. At 300 °C, a 100 // Z0 fiber texture appears, but the general orientation of the grain is random at other temperatures. The detection of mechanical properties found that the elongation of Cu–Sn alloy increasing from 14% to 65% gradually and the yield strength (YS) and tensile strength (TS)decreasing to 282 MPa and 352 MPa respectively.